Trustworthy Leaders in the Thematic Hadith Perspective: An Ideal Concept for Indonesia - Ishak, Nurfaika; Ismail, Laode; Sakka, Abdul Rahman (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
A leader is a person who is trusted by the community to be able to hold responsibility for sustainability in government. In Islam, leaders must be trustworthy as per many narrated hadiths. This research aimed to analyze the basic concept of trustworthy leaders, analyze hadiths that examine trustworthy leaders, and find the ideal concept for trustworthy leaders for Indonesia. The method used is a syar'i approach. The research results show that trustworthy leaders have honest, fair, wise and patient characteristics. Regarding the hadith of trustworthy leaders, it was narrated by Imam al-Hakim, Imam Muslim, Imam Bukhori, Imam Ahmad that every leader will be held accountable, the leader must be competent, fair, honest, not authoritarian, loving and loved by his people. Furthermore, the ideal concept of an Amanah leader for Indonesia is a leader who can accommodate the differences and diversity of Indonesian society with the concept of justice, can exercise authority with the concept of honesty, and can be responsible by applying the concept of accountability.